2018
DOI: 10.1093/pch/pxy072
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of music (Brahms lullaby) and non-nutritive sucking on heel lance in preterm infants: A randomized controlled crossover trial

Abstract: Objectives: This study examined a more effective pain management method, without sucrose, on heel lance in preterm infants using the Premature Infant Pain Profile (PIPP). Design: In a nonblinded, randomized controlled, two-period, two-sequence crossover trial, 25 infants were randomly allocated to intervention (a Brahms lullaby with non-nutritive sucking, facilitated tucking and holding) or standard care (facilitated tucking and holding). Setting: Local Perinatal Medical Centre's NICU in Japan, July 2014 until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Repeated painful procedures in neonates reduce the volume of white and gray matter (Brummelte et al, 2012) and lead to behavioral abnormalities (Grunau et al, 2009;Vinall et al, 2014); these adverse effects may last until adolescence (Nosarti et al, 2002;Nosarti et al, 2008;Anderson & Doyle, 2003;Grunau, Whitfield & Fay, 2004;Schmidt et al, 2010;Loe et al, 2011;Lax et al, 2013;Walker et al, 2018). Many researchers have attempted to relieve the pain of skin puncture in the heel in neonates (Pillai Riddell et al, 2015;Stevens et al, 2017) using interventions such as pacifiers, holding, music, and a combination of these (Gao et al, 2018;Peng et al, 2018;Perroteau et al, 2018;Uematsu & Sobue, 2019;Campbell-Yeo, 2019;Davari et al, 2019). However, some have suggested that the Premature Infant Pain Profile (Stevens et al, 1996;Gibbins et al, 2014) used to evaluate neonatal pain in these studies has issues in terms of pain detection sensitivity (Hartley et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Repeated painful procedures in neonates reduce the volume of white and gray matter (Brummelte et al, 2012) and lead to behavioral abnormalities (Grunau et al, 2009;Vinall et al, 2014); these adverse effects may last until adolescence (Nosarti et al, 2002;Nosarti et al, 2008;Anderson & Doyle, 2003;Grunau, Whitfield & Fay, 2004;Schmidt et al, 2010;Loe et al, 2011;Lax et al, 2013;Walker et al, 2018). Many researchers have attempted to relieve the pain of skin puncture in the heel in neonates (Pillai Riddell et al, 2015;Stevens et al, 2017) using interventions such as pacifiers, holding, music, and a combination of these (Gao et al, 2018;Peng et al, 2018;Perroteau et al, 2018;Uematsu & Sobue, 2019;Campbell-Yeo, 2019;Davari et al, 2019). However, some have suggested that the Premature Infant Pain Profile (Stevens et al, 1996;Gibbins et al, 2014) used to evaluate neonatal pain in these studies has issues in terms of pain detection sensitivity (Hartley et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…When randomised to the Control arm of the study, infants received at least 0.3 mL of Sweet‐Ease Natural Sucrose Solution (24% sucrose and purified water solution) via syringe immediately prior to venepuncture and were allowed to suck a soother. In the Intervention arm, a Bluetooth speaker was placed adjacent to the infant which was pre‐set to play Brahms’ Lullaby Opus 49 No.4, as selected in line with previous similar studies . The music was delivered on a continuous loop at a sound level between 45 and 50 decibels in line with recommendations from the American Academy of Paediatrics (AAP) regarding sound levels in the NICU.…”
Section: Methodsmentioning
confidence: 99%
“…Bluetooth speaker was placed adjacent to the infant which was pre-set to play Brahms' Lullaby Opus 49 No.4, as selected in line with previous similar studies. 26,27 The music was delivered on a continuous loop at a sound level between 45 and 50 decibels in line with recommendations from the American Academy of Paediatrics (AAP) regarding sound levels in the NICU. In cases where the infant was on an open-top resuscitaire for the venepuncture and the ambient noise level exceeded 50 decibels, the sound level was increased to a maximum of 58 decibels.…”
Section: Interventionsmentioning
confidence: 99%
“…on another non-pharmacological intervention. One group of researchers illustrated that the addition of the combination of a lullaby and NNS on top of facilitated tucking and holding significantly reduced pain scores during heel lance ( 97 ). Another group showed that compared to NNS alone, the combination of NNS and mother's milk odor was associated with significantly lower behavioral pain scores during venipuncture and reduced crying after venipuncture ( 98 ).…”
Section: Review Of Non-pharmacological Procedural Pain Management Strategiesmentioning
confidence: 99%